FRP Cables to Prestress RC Beams: State of the Art vs. a Split Wedge Anchorage System - Marco Damiani; Attilio Quadrino; Nicola Nisticò (Buildings, 2021)
Versatility and high performance in terms of specific stiffness and strength, as well as non-corrosive sensitivity, make FRP (Fiber-Reinforced Polymer) cables a viable alternative to steel ones in the development of prestressing systems. On the other hand, the orthotropic and brittle nature of FRPs could trigger a premature failure of the cable in the anchorage system, for which several solutions have been proposed so far in civil structural applications. In this context, after a preliminary state of the art, the work introduces a split wedge anchorage for FRP (ϕ = 12 mm) cables proposing two different solutions for steel wedges having the external surface: either (1) a constant (3 degrees) slope or (2) a double slope obtained by shaping it with an angle of 3.0 degrees before and then of 3.1 degrees along the most tapered part. The goal was to exploit the nominal cable capacity (257 kN), avoiding stress peaks that cause its premature failure. The proposed solutions have been experimentally tested and, as far as the double angle solution is concerned, the failure loads were equal to 222 and 257 kN, denoting that the proposed solution can reach the cable capacity. Clearly, further investigations are needed to check the variability of the results and eventually improve the system.